2010
DOI: 10.5012/bkcs.2010.31.6.1583
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical Applications Based on Carbon Nanotube/Prussian Blue Screen-printable Composite

Abstract: A single step fabrication process of carbon nanotube/Prussian Blue (CNT/PB) paste electrodes based on screen printing technology has been studied as an amperometric sensor for the determination of hydrogen peroxide and free chlorine. Compared to the classical carbon paste (CP) electrode, the CNT paste electrode greatly enhanced the response in the presence of hydrogen peroxide due to the electrocatalytic activity of the CNT. Based on the CNT/binder paste, PB was also incorporated into a network of CNT paste an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…In particular, electrochemical investigations of the glass|FTO|PB sensor as well as optical investigation of the glass|FTO|PW-PB electrode showed that the sensitivity of PB towards FCL is based on FCL-caused oxidation of PW, i.e., PB catalyses the reduction in FCL through the PW form. The glass|FTO|PB sensor displayed linear dependency between FCL concentration and the reduction current in a wide concentration range from 1.7 to 99.2 μmol L −1 of FCL with a sufficient sensitivity of ~0.8 µA cm − 2 μmol −1 L similar to other PB-based amperometric FCL sensors reported [ 45 , 46 , 47 ] and appropriate for FCL concentration monitoring in disinfected water. The main advantage of the sensor developed in this research is its high selectivity towards FCL as chlorate, perchlorate and nitrate ions induce only negligible amperometric response under the working conditions of the sensor.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In particular, electrochemical investigations of the glass|FTO|PB sensor as well as optical investigation of the glass|FTO|PW-PB electrode showed that the sensitivity of PB towards FCL is based on FCL-caused oxidation of PW, i.e., PB catalyses the reduction in FCL through the PW form. The glass|FTO|PB sensor displayed linear dependency between FCL concentration and the reduction current in a wide concentration range from 1.7 to 99.2 μmol L −1 of FCL with a sufficient sensitivity of ~0.8 µA cm − 2 μmol −1 L similar to other PB-based amperometric FCL sensors reported [ 45 , 46 , 47 ] and appropriate for FCL concentration monitoring in disinfected water. The main advantage of the sensor developed in this research is its high selectivity towards FCL as chlorate, perchlorate and nitrate ions induce only negligible amperometric response under the working conditions of the sensor.…”
Section: Discussionsupporting
confidence: 64%
“…There are several articles covering the application of Prussian blue (PB) for the electrochemical detection of FCL [ 45 , 46 , 47 ]. Shim et al used carbon nanotube/Prussian blue screen-printed composite for the amperometric detection of FCL [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations